Effects of ethephon on heartwood formation and related physiological indices of Dalbergia odorifera T. Chen - Zhu, Yuan-Jing; Li, Jia-Wen; Meng, Hui; He, Wen-Jie; Yang, Yun; Wei, Jian-He (Frontiers in Plant Science, 2024)
Dalbergia odorifera T. Chen, known as fragrant rosewood, is a rare and endangered tree species. Studies have shown that plant growth regulators can effectively promote heartwood formation. This study aimed to investigate the effects of ethephon (ETH) on heartwood formation and the influence of ethephon and hydrogen peroxide (H2O2) on the physiological characteristics in D. odorifera. D. odorifera branches underwent treatment with 2.5% exogenous plant hormones, including ETH, jasmonic acid (JA), salicylic acid (SA), abscisic acid (ABA), H2O2, and inhibitors such as ascorbic acid (AsA) to inhibit H2O2 synthesis , and (S) -trans 2-amino-4 -(2-aminoethoxy) -3-butene (AVG) to inhibit ethylene synthesis. After a 14-day period, we conducted an analysis to evaluate the impact of these plant growth regulator on elongation distance, vessel occlusion percentage, and trans-nerol content. Additionally, the effects of ETH and H2O2 on endogenous plant hormones, H2O2 content, soluble protein content, and enzyme activity were investigated within 0-48 h of treatment. After treatment with 2 ETH for 14 days, the extension distance of the heartwood material was 15 cm, while the trans-nerolol content was 15 times that of the ABA group. ETH and H2O2 promoted endogenous ethylene synthesis; Ethylene content peaked at 6 and 18 h. The peak ethylene content in the ETH group was 68.07%, 12.89 %, and 20.87% higher than the initial value of the H2O2 group and ddH2O group, respectively, and 29.64% higher than that in the AVG group. The soluble protein content and activity of related enzymes were significantly increased following ETH treatment. ETH exhibited the most impact on heartwood formation while not hindering tree growth. This treatment effectively triggered the production of endogenous ethylene in plants and enhanced the activity of essential enzymes involved in heartwood formation. These findings serve as a valuable reference for future investigations into heartwood formation.